Urgency of Criminal Liability for Corporations Paying Wages below the Minimum Wage Based on Justice Values - Hendri; Payaman J. Simanjuntak; Teguh Prasetyo (Universitas Pelita Harapan, 2026)
Workers who receive wages below the minimum wage standards do not reflect a sense of justice for employees. This study aims to analyze the current regulation of corporate criminal liability for companies paying below minimum wages, the reasons behind differences in the application of criminal sanctions against corporations in minimum wage cases in Indonesia, and the ideal regulatory framework for corporate criminal liability in such cases based on justice values in the future. To achieve these objectives, this research employs a normative legal method, supported by Lawrence M. Friedman’s legal system theory and theories of justice. The result of this study is the regulation of corporate criminal liability in Indonesia is considered the most comprehensive and repressive, particularly after being strengthened through Law No. 6 of 2023 and the Criminal Code, which recognize corporations as subjects of criminal law and impose sanctions in the form of imprisonment, fines, and additional penalties for violations of minimum wage provisions. Although this regulatory framework serves as an instrument for worker protection, its effectiveness heavily depends on supervision and consistency in law enforcement. Therefore, stronger implementation is required to ensure that sanctions are not merely normative but also provide a deterrent effect and real restitution of workers’ rights. The ideal regulation based on justice values in the future includes: the imposition of sanctions oriented toward restoring workers’ rights; the application of criminal restitution in the form of compensation for workers’ losses, and the implementation of a double track system combining criminal sanctions and enforcement sanctions to enhance effectiveness and deterrence.